SPD-Parteitag 1970 in Saarbrücken; 11.05.1970 - 14.05.1970 (2010)
1. Verhandlungstag am 11.05.1970:<NZ>Fortsetzung Antragsberatung:<NZ>Hermann Heinemann, Protokoll Seiten 106 - 107, 00'01'' - 02'40'';<NZ>Kurt Mattick, Protokoll Seite 108, 02'52'' - 05'43'';<NZ>Hans Apel, Protokoll Seiten 109 - 111, 05'59'' - 14'07'';<NZ>Walter Möller, Protokoll Seite 112, 14'21'' - 16'00'';<NZ>Willy Brandt, Protokoll Seiten 112 - 114, 16'15'' - 21'31'';<NZ>Oswald Paulig, Protokoll Seite 114, 21'37'' - 22'36'';<NZ>Walter Möller, Protokoll Seiten 114 - 115, 22'38'' - 24'03'';<NZ>Oswald Paulig, Protokoll Seite 115, 24'07'' - 24'32'';<NZ>Gert Lüttgert, Protokoll Seiten 115 - 116, 24'45'' - 29'55'';<NZ>Alfred Nau, Protokoll Seiten 116 - 117, 30'12'' - 33'40'';<NZ>Walter Fiebig, Protokoll Seiten 117 - 118, 33'53'' - 35'02'';<NZ>Peter Conradi, Protokoll Seiten 118 - 120, 35'29'' - 39'27'';<NZ>Norbert Gansel, Protokoll Seiten 120 - 124, 39'47'' - 51'33'';<NZ>Helmut Schmidt, Protokoll Seiten 124 - 127, 51'38'' - 60'50''.;